Characterization of phases in an Fe-Mn-Si-Cr-Ni shape memory alloy processed by different thermomechanical methods - Fuster, Valeria de Los Angeles (2015)
The presence of second phases in FeMnSi-based systems has been widely discussed in the literature, and also in our previous works. In this manuscript, various specimens of an Fe-15Mn-5Si-9Cr-5Ni wt.% (nominal composition) shape memory alloy were processed by different thermomechanical treatments in order to identify the phases present in each condition. TEM-EDS results indicate that the chemical composition of the second phase we found in all cases is close to 19Mn-xSi-12Cr-5Ni at. %, with x varying between 5 and 11, and Fe balance. This is compatible with a Fe5Ni3Si2 type intermetallic phase. It forms in a temperature range between 600 and 900 °C, independently of the thermomechanical processing and the coexisting phases. Rietveld refinement of X-ray patterns was done using Maud software, and the phase was found to be isostructural to the pi-phase Cr3Ni5Si2 with space group P213 and lattice parameter equal to 0.6227(7) nm. Phase quantification, crystallite size and accumulated microstrain were also computed as a convenient set of variables, necessary for improving refinement quality. Relevant microstructural information, i.e. stacking fault and twinning probabilities, along with dislocation density, were calculated for austenite, the matrix phase, contributing to the reliability of the determination of the crystallographic characteristics of the second phase.